Analysis Of Added Value Of Fried Bilih Fish In Sumpur Makmur Trade Business, Batipuh Selatan Subdistrict, Tanah Datar Regency, West Sumatra Province - Mita Nursalamah Purba; Zulkarnaini Zulkarnaini; Hendrik Hendrik (Berkala Perikanan Terubuk, 2022)
This research was conducted from June to July 2021 at the Bilih Fried Fish TradingBusiness, Sumpur Makmur, South Batipuh Subdistrict, Tanah Datar Regency, RiauProvince. This study aims to determine the amount of added value generated by the SumpurMakmur Fried Bilih Fish Trading Business and to determine the BEP (Break Event Point)value in the business. The method used in this research is the case study method at theSumpur Makmur Fried Bilih Fish Trading Business, namely the research focused on aparticular case to be observed and analyzed carefully to completion. The respondents in thisstudy were the owner of the Sumpur Makmur Fried Bilih Fish Trading Business. .The results of this study indicate that the added value obtained from UD. Sumpur Makmuris IDR. 32,163,-/kg with a Value Added Ratio of 38.59% Fixed costs incurred forprocessing Bilih fried fish are IDR. 46,583,33,-/one production while variable costsincurred are IDR. 3,667,500,-/one production. The basic price of raw Bilih fish is Rp.50,000,-/kg while the selling price of fried Bilih fish is Rp. 250,000, -/kg so that there is aprofit of Rp. 200,000,-. Break-even point of sales (BEP) occurred in sales of 14.67,/kg orRp.220.933,735,-. In other words, the fried Bilih fish business is quite safe to operate.Considering that basically the business of processing Bilih Fried fish is quite profitable,then to increase the amount of profit it can be attempted by producing above the break-evenpoint by increasing the amount of production product.